Washout of hepatocellular carcinoma on portal venous phase of multidetector computed tomography in a pre‐transplant population. Issue 6 (4th August 2015) - Kitzing, Yu Xuan; Ng, Bernard HK; Kitzing, Bjoern; Waugh, Richard; Kench, James G; Strasser, Simone I; McCormack, Samuel
Abstract: Introduction: Washout is an important diagnostic imaging feature of hepatocellular carcinoma (HCC) on computed tomography (CT). The primary aim of this study is to evaluate the prevalence and the interobserver variation in the detection of portal venous phase (PVP) washout of HCCs using CT in a transplant population. The secondary aim is to evaluate factors influencing the detection of PVP washout. Methods: Forty‐five patients who underwent CT liver imaging within the 60 days before transplantation had viable HCCs confirmed on pathology. Two radiologists retrospectively reviewed the images for HCCs including features of arterial enhancement and PVP washout. Clinical data, peak kilovoltage, imaging features of portal hypertension, region of interest attenuation measurements of the individual lesions, background liver parenchyma and portal vein were obtained. Liver to lesion attenuation ratio was also calculated. Statistical analysis was performed. Results: The two readers identified 50 arterially enhancing HCCs in 45 patients. In consensus, the two readers identified washout in 60% of the HCCs with a substantial interobserver agreement (kappa = 0.633). PVP washout was associated with larger lesion size, increased background liver parenchyma attenuation, increased liver to lesion attenuation ratio, increased portal vein attenuation and hepatitis B viral status ( P  = 0.027, 0.008, 0.014, 0.017 and 0.037 respectively). Conclusion: In our transplant population, portal venous phase washout was seen in 60% of the hypervascular HCCs. Factors influencing the presence of PVP washout include lesion size as well as the liver and portal vein attenuation reflective of the portal haemodynamics.